Thromboembolism and anticoagulation management in the preterm infant. Issue 1 (February 2016) - Rajagopal, Revathi; Cheah, Fook-Choe; Monagle, Paul
Summary: The incidence of preterm thromboembolism has been increasing due to advances in diagnostic imaging which allow better detection of thrombi in sick preterm infants. At the same time, improvement in neonatal intensive care unit supportive care has increased the number of surviving and living preterm infants with thromboembolic risk factors. Disruption in the fine balance of hemostasis with potential risk factors, specifically septicemia and indwelling catheters, increase the occurrence of thromboembolic events. Treatment strategies in preterm infants are challenging due to limited data.